Keefektifan Model Pembelajaran Scramble dengan Permainan Teka-Teki Silang terhadap Pemahaman Cerita Rakyat - Hana Puri, Nur Adha Praba; D. H., Dwi Prasetiyawati; Azizah, Mira (Jurnal PGSD, 2019)
The background that drives this research is the low understanding of students about folklore. This is due to learning that only uses lectures and discussions so learning becomes less innovative. Based on this, the scramble learning model with crossword puzzles can be used as an alternative to innovative and fun learning. The purpose of this study is to find out and analyze the effectiveness of the scramble learning model with crossword games on understanding fourth grade folklore in elementary school. This research uses quantitative methods in the form of quasi experimental design with nonequivalent control group design. The problem in this study is the low understanding of students about folklore. The data of this study were obtained through questionnaires, observations, and interviews. This research was conducted in class IV at SD N Tlogosari Wetan 01 Semarang. This study produced   = 6.5016 and the coefficient was significant at the level of 5% and dk = 70, then obtained  = 1.99394 so the value of > and increase in the average learning outcomes from the control class posttest of 61.25 with results the experimental class posttest was 82,083. The completeness of classical learning in the experimental class shows 94.44% of students who complete with a total of 34 out of 36 students. So that it can be said as a scramble learning model with an effective crossword game on understanding the fourth grade folklore.Keywords: Scramble Learning Model, Cross Puzzle Game, Understanding Folk Stories